China's search for indigenous industrial development : a case study of the aviation industry - Zhang Yan, N. (Cranfield University, 2009)
The one common feature amongst all underdeveloped nations is their intent to develop. The question is how to achieve this goal in the most efficient and effective manner. China’s recent premier, Deng Xiaoping, captured this challenge in what has become a celebrated metaphor …“It does not matter whether the cat is black or white; as long as it catches the mouse, it is a good cat.” For China, the choice of development strategy has not been Communism or Capitalism, but rather a mixture of both with central direction and decentralized profit incentives combined. This unique model was launched at the time of the 1978 ‘Open-Door’ policy and heralded a period of unparalleled growth and development. Access to technology to support the creation of modern industries came through foreign investment, and China’s central planners were in a strong position to direct inward technology transfer to what were held to be the ‘back-bone’ industries essential for high technology industrialization. The purpose of this dissertation, then, is to analyse China’s development process, with particular reference to the development of the high technology aviation industry. Aviation (commercial aircraft production) is part of the broader industrial sector, aerospace. This represents one of the highest technology sectors, embracing knowledge-intensive activity, innovation, high skills and high value-added. Aviation is regarded as a strategic industry, and as such, China has viewed foreign technology not only from a development perspective, but also as a vehicle for achieving sovereignty and sustainability. In other words, China’s long-term aim has been to develop an ‘indigenous’ aviation industry. However, such aviation ambitions are shared by several other Asian nations, including Japan, Singapore, South Korea, Malaysia and Indonesia. This thus makes the task of gaining technology from the major aviation giants, such as Boeing and Airbus, very competitive. Moreover, the drive to build commercial aircraft has both an economic and a nationalistic dimension, and so ‘success’ carries not profit but political rewards, also. ii In evaluating the challenge Asia faces in developing an indigenous aviation industry, secondary and primary data were gathered, providing a sense of country strategy and performance. Japan is the technology leader, with countries playing the role of technology followers. China, however, is at the back of the pack, with limited local capacity and constrained indigenous capability. However, notwithstanding the country’s ‘chaotic’ industrial development history over the last 50 years, the present powerful combination of high economic growth, massive demand for commercial air travel - and thus airliners, unlimited central government resources, command planning and an absolute commitment to succeed, suggests that China is strongly positioned to replace Japan as the aviation technology leader in the years to come.